Two new corals from the Koneprusy Limestone (Lower Devonian, Pragian, Barrandian, Czech Republic) - Galle,A.; Hladil,J.; May,A. (Journal of the Czech Geological Society, 1999)
Two new species, one of them considered a new genus, are described from the Pragian Koneprusy Limestone. Members of the new genus display characters of both disphyllids and phillipsastraeids. Ecology and sedimentology of the Koneprusy Limestone is briefly discussed and the morphology of the Koneprusy reef is mentioned.
Keywords: Tabulata; Rugosa; new species; new genus; reef morphology; limestone sedimentology